Study to access the socio-demographic determinants and the reasons for preference of place of delivery in rural women of Paithan, Aurangabad (Maharashtra) - Kuril, Bina M.; Pund, Sandeep B.; Doibale, Mohan K.; Ankushe, Rajendra T.; Kumar, Purushottam; Siddiqui, Nafeha (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal health reflects the overall effectiveness of the health system of any country. One strategy for reducing maternal mortality and morbidity is ensuring that every baby is delivered in an institution. Government of India has launched various health schemes under the umbrella of National Rural Health Mission (NRHM) to promote institutional deliveries. Thus this study was conducted to study the socio-demographic determinants of place of delivery and the reasons for preference of place of delivery by rural women. Methods: A community based cross-sectional study was conducted in the field practice area of rural health training center (RHTC), Paithan, Dist. Aurangabad during the period of 1st October 2015 to 31st March 2016. All the villages under two sub-centers of one PHC under the RHTC were selected for the study. All women above 18 years of age who delivered at least once between 1st January 2001 to 31st December 2015, were interviewed for their place of delivery and their socio-demographic profile. Results: It was observed that 564 (80.46%) women were delivered in a hospital, of which 313 (44.65%) and 251 (35.81) were delivered in private and government institutions respectively, while 137 (19.54%) respondent women were delivered at home. Education of women, occupation of women, type of Family, education of husband, occupation of husband, parity, distance of hospital from the residence and women’s age at marriage were the socio-demographic factors found to be significantly associated with place of delivery by the bivariate analysis. Reasons observed for home delivery were related to lack of knowledge about government healthcare facilities, about need for institutional delivery and inability to reach hospital on time. Conclusions: The proportion of home deliveries in 2001-15 was 13.08% as against 35.80% of government institutional deliveries and 44.65% of private institutional deliveries. Education of women, education and occupation of husband were found to be significantly associated with place of delivery by multivariate analysis.